Aktual'nost' prognosticeskoj ocenki serdecnoj dejatel'nosti u sportsmenov-futbolistov - Minina, E. N.; Lastovetsky, A. G.; Bobrik, Y. V.; Minin, V. V.; Kurbetdinova, Z. R. (Teorija i Praktika fiziceskoj Kul'tury, 2018)
Excessive physical loads and stress in the training and compettitive processes in combination with other risk factors lead to myocardial disorders, and sometimes to cardiovascular disorders. Prognostic ratings of cardiac activity in football are designed with application of integral highly-informative sets of markers to trace, on an off-clinical basis, potential cardiovascular system disorders in the training process to both prudently manage the training loads and analyze the myocardial responses to regular trainings and competitive stresses. 25 footballers were sampled for the study. We applied a computerized PHASOGRAP® test system to read and analyze the ECG data, with the single-channel ECG data being processed in the phased space with application of the computer graphics and automatic pattern recognition technologies. Analyzed in the data processing procedure were a few parameters of the phased pattern including its symmetry versus the T-peak of the single-channel ECG (bT, units). The individual functionality was rated by the maximal/ moderate test loads with application of an instant mobile gas analyzer Oxycon Mobile (Jaeger) and MetaMax 3B (Cortex) system. The individual heart rates versus loads were tested by Polar pulsometer (Finland-made). Objective of the study was to analyze benefits of the prognostic ratings of cardiac activity in modern football using the cardiac activity phase measurement tools. The study data showed correlation of the quiescent-state T-peak symmetry with the maximum oxygen consumption sagging rate. Based on the study data, we developed a values matrix to instantly rate the individual functionality and competitive fitness in football trainings.